The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.7705/biomedica.v31i1.330
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la actividad tóxica de los insecticidas piretroides deltametrina y lambdacihalotrina en dos poblaciones de campo de Rhodnius pallescens (Hemíptera: Reduviidae) de Panamá

Abstract: Introducción. La evaluación de la sensibilidad de las poblaciones de Rhodnius pallescens permite detectar y vigilar los grados de resistencia en el transcurso del tiempo, con el fin de evaluar los efectos de las estrategias de control y manejo de la resistencia. Objetivo. Determinar la línea base de sensibilidad de los principios activos deltametrina y lambdacihalotrina en ninfas de estadios I y V, en dos poblaciones de campo de R. pallescens. Materiales y métodos. Los bioensayos se realizaron tomando como ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Although the inattention to CHD by MINSA is likely due to the enzootic epidemiologic characteristic and chronic nature of CHD [ 2 ], some researchers attribute it to a significant degree of underreporting, and to the non-domiciliary behavior of R. pallescens in Panama [ 101 , 103 ]. For instance, Panamanian populations of R. pallescens are highly susceptible to deltamethrin and lambda-cyhalothrin, but it is impractical to implement pyrethroid residual spraying to kill a vector that does not reside indoors [ 113 ]. CHD prevention and control programs in Panama must focus on putting into action an active surveillance program for accurate case detection.…”
Section: Introductionmentioning
confidence: 99%
“…Although the inattention to CHD by MINSA is likely due to the enzootic epidemiologic characteristic and chronic nature of CHD [ 2 ], some researchers attribute it to a significant degree of underreporting, and to the non-domiciliary behavior of R. pallescens in Panama [ 101 , 103 ]. For instance, Panamanian populations of R. pallescens are highly susceptible to deltamethrin and lambda-cyhalothrin, but it is impractical to implement pyrethroid residual spraying to kill a vector that does not reside indoors [ 113 ]. CHD prevention and control programs in Panama must focus on putting into action an active surveillance program for accurate case detection.…”
Section: Introductionmentioning
confidence: 99%
“…As other authors have mentioned,differences in cuticle thickness (29) in stage I and V nymphs can affect the susceptibility to external stimuli; for instance, Reyes, et al (30), observed that the pyrethroid insecticides (beta-cypermethrin and fenitrothion) were more effective in stage I T. dimidiata and T. maculata nymphs than in stage V ones. Cáceres, et al (31), found that stage I R. pallescens nymphs were sensitive to deltamethrin and lambda-cyhalothrin in different geographical zones. In another study, Germano found similar results (23) in toxicity bioassays with deltamethrin in different stages of development in T. infestans.…”
Section: Girgensohnine Analoguesmentioning
confidence: 99%